Cultural and Historical Preservation through Onomastic Materials: A Case of Toponyms and Anthroponyms in Kinyarwanda - Jacques Lwaboshi Kayigema (The Institute of Academic Research and Publication (IARP), 2021)
Proper names, also linguistically called toponyms and anthroponyms, embed extensive sociolinguistic, cultural, and historical aspects in the life of any nation. Thus, they have caught the researcher’s attention because of the cultural and historical heritage they preserve in the context of language contact. From one place to another, and one specific period to another, anthroponyms and toponyms offer a wide range of research because of the scientific curiosity researchers have as to know why the name of a person or place exists, where it comes from, who named it, and when it was named so. In other words, the research is carried within spatial and temporal scope. Anthroponymy is the study of proper names of human beings, both individual and collective, while toponymy is the study of proper names of places. This paper aims at showing how place and person names embed cultural and historical features necessary to understand, explain, and preserve a people’s culture and history for a given period. The method used to research this topic is descriptive and it is based on the materials observed from various sources such as street names, hoardings, individual names, just to name a few. Therefore, this study focuses on specific topologies and periods, i.e. names denoting locations where the Rwandan territory has extended in the precolonial, colonial, postcolonial periods, and post-genocide periods.